The role of intravenous iron sucrose treatment in patients with iron deficiency anemia in pregnancy: A prospective controlled cohort study - Eraslan Şahin, Mefkure; Çöl Madendağ, İlknur (Journal of Surgery and Medicine, 2019)
Aim: Iron deficiency anemia is the most common nutritional disorder in pregnancy and approximately 40% of all pregnant women are complicated with perinatal morbidity and mortality. In this work, the efficacy of intravenous iron sucrose and oral iron hydroxypolymaltose is compared in third-trimester pregnancies with iron deficiency anemia. Methods: A prospective cohort study is planned. A total of 140 pregnant women were enrolled in the study in two groups. The first group consisted of patients who could not tolerate oral iron therapy and were treated with intravenous iron sucrose and the second group was composed of patients who used oral iron III hydroxy polymaltose for anemia treatment in third trimester.. The treatment effects of blood count parameters were compared between groups. Results: Demographic and baseline characteristics were similar in both groups. Mean hemoglobin levels before treatment were 9.03±0.47 g/L in the intravenous treatment group and 8.82±0.39 g/L in the oral treatment group. 30 days after treatment, the mean hemoglobin levels were 10.7±0.55 g/L in the intravenous treatment group and 10.9±0.58 g/L in the oral treatment group. Before delivery, the mean hemoglobin levels were 11.38±0.56 g/L in the intravenous treatment group and 11.35±0.47 g/L in the oral treatment group. There was no significant difference between groups for hemoglobin levels before treatment, 30 days after treatment, and before delivery (p=0.355, p=0.513, and p=0.975, respectively). The mean mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) levels were not statistically different between groups before treatment, 30 days after treatment, and before delivery. Conclusions: Intravenous administration of iron sucrose is an alternative to blood transfusion for the treatment of pregnant women with iron deficiency anemia during the third trimester.